AYN RAND AND THE COGNITIVE REVOLUTION IN PSYCHOLOGY. - Campbell, Robert L. (Journal of Ayn Rand Studies (Journal of Ayn Rand Studies Foundation))
ROBERT L. CAMPBELL explains how Ayn Rand's epistemology drew on ideas and findings from the Cognitive Revolution, the change in American psychology during the 1950's that re-established mental processes as an object of study and overthrew behaviorism. Particularly noticeable is Rand's reliance on George Miller's conclusions regarding limited cognitive capacity, and her broad agreement with Noam Chomsky's devastating critique of B. F. Skinner's behaviorism. Both Rand's points of contact-and differences-with the Cognitive Revolution are discussed. Once the impact of the Cognitive Revolution on Rand is recognized, her insistence that philosophy owes nothing to psychology becomes harder to defend.